Correlates of Alcohol Consumption among Adolescents in Ibadan North Local Government Area of Oyo State, Nigeria - Adenugba, Adebimpe A.; Ijagbone, Ibhade Omonigho (Richtmann Publishing, 2012)
Alcohol consumption is a behavioural problem defined relative to age and is considered problematic below a certainage or stage in life. Young people by virtue of their stage in development are likely to engage in drinking alcohol. The aim of thepaper is to examine the correlate of alcohol consumption among adolescents in Ibadan North Local Government area of OyoState, Nigeria. The paper was based on the social action theory and it adopted the survey design and multi-stage samplingprocedure to elicit information from 313 adolescents. Some of the findings revealed that males were more predisposed to alcohol consumption.71.9% of males had drunk alcoholcompared to 32.5% females’ counterparts. Males who still drink alcohol prior to the study were higher than females (47.2%compared to 15.8%). The hypothesis revealed that there was no significant relationship between peer pressure and alcoholconsumption. Another hypothesis revealed that marital status, high level of education mother’s occupation, father’s highesteducation and father’s occupation had positive correlation with alcohol consumption. Ethnicity, religious affiliation, occupation,persons living with and type of house showed a negative correlation toward alcohol consumption with only religion having asignificant relationship. This shows that socioeconomic status will jointly and independently affect alcohol consumption. Thepaper concludes that males should be warned about the implications of alcohol consumption since they are likely to be morepredisposed to alcohol than females, career counselors must encourage students to abstain from high levels of alcoholconsumption so that they may be focused in life.